Kandungan Kadar Garam dan Susut Masak Bakso Daging Ayam Broiler pada Penambahan Putih Telur Sebagai Bahan Pengenyal pada Konsentrasi yang Berbeda - Santriyono, Santriyono; Muh. Jurhadi, Muh. Jurhadi; Nurhaeda, Nurhaeda (Fakultas MIPA UNM, 2019)
Abstract. The objective of the research was to find out the effect of adding egg white as the tough material to the salt content and cooking shrinkage of meatballs. The research was held on July to August 2018 in the laboratory of agriculture, animal farm, and fishery faculty, Muhammadiyah university of Parepare and continued analysis of salt content in the live stock chemical laboratory of animal farm Faculty, Hasanuddin Makassar University. The researcher used broiler meat, water, flavoring, garlic, pepper, salt, egg white and ice cube. The method used was a Completely Randomized Design with 4 treatments and 3 repetitions, that is T0 = without tough material, T1 = 15 grams of egg white, T2 = 43 grams of egg white, T3 = 74 grams of egg white. The research result showed that the addition of egg white as the tough material at different concentration have a real impact to the salt content and cooking shrinkage after being continued with the Duncan test it was found that there were differences and significantly affected the salt content and cooking shrinkage meatballs. Keywords: meatballs, chicken meat, egg white, salt content, cooking shrinkage